INNOVATIVE METHOD FOR TREATING PERIODONTAL DISEASES USING PLASMOLIFTING (Ustozlar uchun, 2025)
In order to find new effective ways to treat chronic generalized severe periodontitis, we carried out complex conservative treatment of 34 patients, which, in addition to standard therapy, included the following combination: hardware removal of dental plaque and Plasmolifting technology. The absence of clinical signs of inflammation, a stable level of hygienic indices during the entire observation period and a reduction in the depth of the periodontal pocket confirmed the high effectiveness of conservative therapy for severe periodontitis with the developed therapeutic complex.